Proceedings of the 27th Conference on l'Interaction Homme-Machine 2015
DOI: 10.1145/2820619.2820637
|View full text |Cite
|
Sign up to set email alerts
|

Designing the user interface of a virtual needle insertion trainer

Abstract: In interventional radiology, inserting a needle to perform a biopsy requires a high haptic sensitivity. The traditional learning methods based on observation of skilled clinicians and training on real patients are questionable. Virtual Reality (VR) surgical simulators have previously been shown to be efficient for training. However, there is a lack of guidelines to ensure the fidelity of these simulators. In this paper, an iterative design approach is used to design and evaluate the user interface for a VR nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The obtained grade can be used in statistical tests. Among the most widespread tests in studies of haptic devices are the analysis of variance (ANOVA) [35][36][37], the Mann-Whitney U test [38][39][40][41] and the Friedman test [42,43].…”
Section: Experimental Task Planningmentioning
confidence: 99%
“…The obtained grade can be used in statistical tests. Among the most widespread tests in studies of haptic devices are the analysis of variance (ANOVA) [35][36][37], the Mann-Whitney U test [38][39][40][41] and the Friedman test [42,43].…”
Section: Experimental Task Planningmentioning
confidence: 99%
“…The literature provides evidence that the projected hand, when synchronized with the real hand, is beneficial in motor tasks. For example, in the biopsy procedure Benyahia et al (2015) and Nguyen, Lakhal e Chellali (2015) showed that the non-animated virtual hand increased the participant's feeling of accuracy when manipulating the virtual syringe. The authors also argued that the virtual hand increases the depth perception providing additional spatial cues to the trainers in the virtual environment.…”
Section: Discussionmentioning
confidence: 99%